1957
DOI: 10.1002/ar.1091280207
|View full text |Cite
|
Sign up to set email alerts
|

The injection of the blood vascular system of the uterus

Abstract: The first detailed .microscopic study of the uterine vasculature by Freund ('04) showed that completc injections are difficult to obtain. He found it necessary to wait for from one to 4 days after death o r removal surgically in order to obtain satisfactory preparations. Injection mass appears to have reached the endometrium in only 6 of his 23 adult specimens. Recently, Hasner ( '46), Dalgaard ( '46), and Schlegel ( '46) had to resort to similar delays ; the last mentioned had, in addition, to use pressures u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1961
1961
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…high blood flow impedance of the uterine radial arteries (Miwa et al, 2009). Early studies demonstrated that, after ovulation, the spiral arteries constrict preemptively to diminish blood flow to the functional layer (Rossman and Bartelmez, 1957). Nevertheless, a thinned or absent functional layer may subject the embryo to higher vascularity from the basal endometrium, which might explain the reduction of implantation caused by elevated oxygen tension and the production of detrimental reactive oxygen species (Catt and Henman, 2000;Yang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…high blood flow impedance of the uterine radial arteries (Miwa et al, 2009). Early studies demonstrated that, after ovulation, the spiral arteries constrict preemptively to diminish blood flow to the functional layer (Rossman and Bartelmez, 1957). Nevertheless, a thinned or absent functional layer may subject the embryo to higher vascularity from the basal endometrium, which might explain the reduction of implantation caused by elevated oxygen tension and the production of detrimental reactive oxygen species (Catt and Henman, 2000;Yang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The basal layer consists of large spiral arteries and is maintained throughout the menstrual cycle, whereas the functional layer includes relatively fine spiral arteries and changes throughout the menstrual cycle. After ovulation, the spiral arteries within the functional layer shrink, causing oxygen tension to decrease in the functional layer, which supports a favorable environment for embryo implantation [8]. If the functional layer is inadequately developed, embryos are close to the large spiral arteries within the basal layer; thus, embryos are exposed to a highly oxygenated environment.…”
Section: Discussionmentioning
confidence: 99%
“…1) published by Bartelmez in 1957 (15), the functional layer of the endometrium has a vascular capillary structure, in contrast to the larger spiral arteries in the basal layer. Other early studies demonstrated constriction of the spiral arteries after ovulation, with diminished blood flow to the surface endometrium (16). One would presume that blood flow and, therefore, oxygen tension would be reduced in the functional or surface epithelium after ovulation and around the time of implantation.…”
mentioning
confidence: 97%